THE PRAGMALINGUISTICS OF APOLOGIZING IN THE ARABIC LANGUAGE BY NON-NATIVE SPEAKERS - Al-rawafi, Abdulkhaleq (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2020)
Learners of a second language struggle to select and produce appropriate different kinds of speech acts due to their complexity. The students of the Islamic boarding schools are assigned to acquire two non-native languages compulsory and concurrently, namely Arabic and English. This study adapts the descriptive analytical approach to investigate the pragmalinguistic of the speech acts of apologizing in the Arabic language as produced by non-native speakers with special focus to the IFIDs. The participants are 202 students recruited to fill in a DCT that consists of eight situations regarding the students’ violation of the rules of the school. The results show that the students tend to use certain semantic formulas of apologies due to their lack of linguistic proficiency. To conclude, these forms are template slots of the IFID in which the non-native apologizer can slot his/her apology within these templates, and hence, enrich their pragmatic competence ability.